Application of Swedish Massage Therapy on Reducing Blood Pressure in Elderly with Hypertension at BPSTW Budi Luhur: A Nursing Case Study - Nur Fatimah, Tri; Indah Yulitasari, Brune (Nursing Case Insight Journal, 2026)
Hypertension is a common cardiovascular disease in the elderly and is known as a "silent killer" because it often causes no symptoms. Uncontrolled hypertension can increase the risk of cardiovascular complications and reduce the quality of life in the elderly. One non-pharmacological therapy that can be used as a complementary therapy to help lower blood pressure is Swedish massage. This study aimed to determine the effect of Swedish massage therapy on reducing blood pressure in elderly patients with hypertension at BPSTW Budi Luhur, Yogyakarta Social Services. The method used was a descriptive case study involving two elderly respondents. Nursing care was provided for three consecutive days, applying Swedish massage therapy interventions. Blood pressure measurements were taken using a sphygmomanometer before and after 30 minutes of Swedish massage using effleurage, friction, petrissage, and tapotement techniques. Two nursing diagnoses were identified: acute pain and disturbed comfort. After three days of Swedish massage intervention, the average blood pressure before intervention was 163/101 mmHg, and after intervention it was 154/99 mmHg, with a reduction of 8 mmHg in systolic blood pressure and 2 mmHg in diastolic blood pressure. These results indicate that Swedish massage can be used as a non-pharmacological complementary therapy to help reduce blood pressure in elderly patients with hypertension